2004
DOI: 10.1074/jbc.m310858200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Four Genes Necessary for Biosynthesis of the Modified Nucleoside Queuosine

Abstract: Queuosine (Q) is a hypermodified 7-deazaguanosine nucleoside located in the anticodon wobble position of four amino acid-specific tRNAs. In bacteria, Q is produced de novo from GTP via the 7-deazaguanosine precursor preQ 1 (7-aminoethyl 7-deazaguanine) by an uncharacterized pathway. PreQ 1 is subsequently transferred to its specific tRNA by a tRNA-guanine transglycosylase (TGT) and then further modified in situ to produce Q. Here we use comparative genomics to implicate four gene families (best exemplified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 31 publications
2
134
1
Order By: Relevance
“…Representatives of the known preQ 1 riboswitch class ) are often located upstream of a Q biosynthetic operon (Reader et al 2004), but some also have been identified upstream of other genes encoding proteins otherwise not associated with Q, and one of these gene types is classified as COG4708. Thus, we speculated that COG4708 proteins might be involved in transporting Q biosynthetic precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Representatives of the known preQ 1 riboswitch class ) are often located upstream of a Q biosynthetic operon (Reader et al 2004), but some also have been identified upstream of other genes encoding proteins otherwise not associated with Q, and one of these gene types is classified as COG4708. Thus, we speculated that COG4708 proteins might be involved in transporting Q biosynthetic precursors.…”
Section: Introductionmentioning
confidence: 99%
“…1). Using comparative genomics, QueF was identified as an enzyme family involved in Q biosynthesis (Reader et al, 2004). QueF is an NADPHdependent oxidoreductase that carries out the unprecedented reduction of a nitrile group (preQ 0 ) to a primary amine (preQ 1 ; Van Lanen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1A). The first step catalyzed by GTP cyclohydrolase I (GCHI; FolE) is shared with the tetrahydrofolate synthesis pathway (10), and then three enzymes-6-carboxy-5,6,7,8-tetrahydropterin synthase (QueD), 7-carboxy-7-deazaguanine synthase (QueE), and 7-cyano-7-deazaguanine synthase (QueC)-lead to the formation of the preQ 0 moiety (11,12) (Fig. 1A).…”
mentioning
confidence: 99%